ACADEMIC SOCIAL CAPITAL AND INSTITUTIONAL TRANSFORMATION OF ISLAMIC HIGHER EDUCATION IN INDONESIA - Kafid, Nur; Rohmatika, Arina (AKADEMIKA: Jurnal Pemikiran Islam, 2019)
Abstract This study aims to see the potential and positioning of IAIN Surakarta, amid the trend of institutional transformation of Islamic Higher Education in Indonesia. In fact, transformation is not merely a matter of changing institutional status, but also the scientific quality of its civitas academics in responding to the technological developments and to the complexity of modern society’s problems. Based on the qualitative approach, wherein the data is obtained from 10 key informants which are determined through the purposive sampling method, the results of this study show that institutional transformation requires the readiness of all resources as its academic social capital. Started from good and appropriate mapping, management and resource development, in accordance with the quality standards determined. However, all of these will not work well without comprehensive institutional policies. Policies that refer to the strategic development plans, and completed with various rules, achievements, and indicators. Keywords: Islamic higher education, and Institutional transformation